Volatile-mediated plant interactions: an innovative approach to cultivar mixture selection for enhanced pest resilience - Markovic, Dimitrije; Seimandi-Corda, Gaëtan; Harizanova, Vili; Stoeva, Atanaska; Himanen, Sari; Saussure, Stephanie; Radonjic, Andja; Đurić, Gordana; Lalićević, Ivana; Kheam, Sokha; Rensing, Merlin; Gallinger, Jannicke; et al. (Frontiers in Plant Science, 2025)
Mixing different cultivars has been recognized as a promising strategy for the reduction of pest pressure and the enhancement of crop performance. However, this applies only in specific combinations, creating a need to select cultivars that interact synergistically in mixtures. We propose a trait-based laboratory method to identify complementary pairs of cereal cultivars based on their ability to prime one another’s defense response through volatile organic compounds (VOCs). In this study, we screened 25 locally-grown cultivars from six European countries to assess their responsiveness to volatile priming under controlled conditions. The tested cultivars exhibited three primary types of volatile interactions: no interaction, one-way interaction (where one cultivar responded to volatiles from another) and two-way interaction (where both cultivars reciprocally responded). Subsequently, the efficacy of these cultivar pairs was evaluated over a three-year period in field trials where aphid infestation, natural enemy abundance and plant traits (height, number of plants per 1-meter, Thousand Grain Weight (TGW) and yield) were assessed. Field trials results demonstrated that only specific cultivar mixtures led to a significant reduction in aphid infestation, indicating a robust genetic and environmental interaction. Mixtures in which both cultivars exhibited two-way interaction under controlled conditions, demonstrated reductions in aphid abundance in comparison to monoculture controls. In contrast, the abundance of natural enemies was not significantly affected by cultivar mixtures, and there were no notable changes in plant traits. We propose that the strategic pairing of cultivars, which actively engage in volatile interactions in the laboratory, can effectively reduce aphid pressure in the field without compromising plant traits or crop yield, thereby reducing reliance on chemical control. Given the role of aphids as vectors of economically significant viruses, reducing their population could also limit the spread of plant diseases in the field. This approach underscores the importance of understanding plant interactions at a chemical level to optimize cultivar pairing and develop sustainable pest management strategies.